(untitled) (REMUNOM, 2023)
Klebsiella pneumoniae is a pathogen that is difficult to manage. Its strains can present various levels of resistance to the antimicrobials used to treat it, such as penicillins, antimicrobials, carbapenems, among others. Therefore, therapeutic capacity is limited, and it is of the utmost importance to study and elucidate the pathogenic and resistance mechanisms associated with K. pneumoniae, so that there can be better therapeutic intervention. In this way, the use of natural plant-based products is a treatment option to be considered. The aim of this study was to evaluate the association of Lavandula hybrida grosso essential oil with synthetic antimicrobials against Krebsiella pneumoniae. The association test was carried out using the diffusion technique using Klebsiella pneumoniae strains (KP 101, KP 102, KP 103 and KP 104) from the Microbiology Laboratory of the Biological Sciences Academic Unit of the Center for Health and Rural Technology at the Federal University of Campina Grande. Next, the essential oil of Lavandula Hybrida Grosso, purchased from Quinare, was combined with the antimicrobials ampicillin and gentamicin (10 μg/mL). For most of the strains analyzed and the antimicrobials used, the essential oil had a synergistic effect. Thus, the association of Lavandula essential oil with synthetic antimicrobials may be an option for use in pharmacology, but further studies are needed to confirm this hypothesis.